Preclinical Evaluation of the Tumorigenic and Immunomodulatory Properties of Human Bone Marrow Mesenchymal Stromal Cell Populations with Clonal Trisomy 5. (19th August 2022) - Marodin, Maria Susana Joya; Godoy, Juliana A.; Alves-Paiva, Raquel M.; Alvarez, Kelen; Mitsugi, Thiago Giove; Krepischi, Ana Cristina Victorino; Hamerschlak, Nelson; Bortolini, Maria Augusta Tezelli; Castro, Rodrigo; Kondo, Andrea T.; Kutner, Jose Mauro; Okamoto, Oswaldo Keith
Abstract : Cytogenetic aberrations may emerge in human mesenchymal stromal cells (MSC) during ex vivo expansion for cell therapy. We have detected clonal trisomy 5 in two distinct autologous MSC products expanded from bone marrow which, based on the current quality control criteria, could not be released for clinical use. Although a safety concern, it is still unclear to what extent recurrent aneuploidies detected in MSC products may affect the threshold for neoplastic transformation or the medicinal properties of these cells. We have carried out an exploratory preclinical study to evaluate these MSC products with clonal trisomy 5, regarding their oncogenic and immunomodulatory potential. Cell population growth in vitro was reduced in MSC cultures with clonal trisomy 5 compared with the population growth of their euploid MSC counterparts, based on a lower cumulative population doubling level, reduced cell proliferation index, and increased senescence-associated beta-galactosidase activity. Subcutaneous injection of clinically relevant amount of MSC population, either with or without clonal trisomy 5, did not generate tumors in immunodeficient mice within a follow-up period of six months. Most importantly, MSC population with clonal trisomy 5 kept immunomodulatory properties upon interferon gamma (IFN γ ) licensing, displaying overexpression of IDO, CXCL9, CXCL10, and CXCL11, in a similar fashion than that of IFN γ -licensed euploid MSC. Our findings suggest that bone marrow MSC products with clonal trisomy 5 may retain their therapeutic potential, based on poor tumor initiating capability and preserved immunomodulatory potency. This preclinical evidence may further support the definition of release criteria of autologous MSC products for cell therapy under critical clinical scenarios. This trial is registered with Clinical Study registration number: RBR-29x2pr .